2(2p-3)-18=

Simple and best practice solution for 2(2p-3)-18= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2p-3)-18= equation:


2(2p-3)-18=0

We simplify the equation to the form, which is simple to understand
2(2p-3)-18=0

Reorder the terms in parentheses
+(+4p-6)-18=0

Remove unnecessary parentheses
+4p-6-18=0

We move all terms containing p to the left and all other terms to the right.
+4p=0+6+18

We simplify left and right side of the equation.
+4p=+24

We divide both sides of the equation by 4 to get p.
p=6

See similar equations:

| n-14=8n | | 0=1.77x+187 | | 4x^2-19+12=0 | | 9(3a+1)a=2 | | 2b-5-9b-3= | | (x+3)2=64 | | 24-1/2=0 | | 6x+10=-68-7x | | 0,4(2x-7)+1,2(3x+0,7)=1,6x | | 04(2x-7)+1,2(3x+0,7)=1,6x | | 12x-24=-36 | | z+4=-10 | | 12+8n=20 | | 8x^3+14x^2-4x= | | 9x-52=5x-8 | | -9(5x+6)+6= | | 7+6(u-6)+5u=2(5u+12) | | -2n+4(5-n)=2(2n+30) | | 2z+1/4=3/4 | | 5+2n=7-4n | | 2x+3-x-1=9x+4-6x-6 | | 2x-6x+7=2x+31 | | -3+5x+1-2x=-3+6x+5-4x | | -4(2x+9)+2= | | 4y+12=24 | | 0.25(4s-2)+2=0.25(3s-9) | | 2(3x-2)-3(x+3)=0 | | -8p+7+9p=12 | | -5(3x+9)+9= | | 199-3x=24x+23 | | 4x+(x+7)=-14-2x | | 3p+4p-2p=20 |

Equations solver categories